2010
DOI: 10.1246/bcsj.20090240
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Structures, and Physical Properties of Tetrakis(alkylthio)tetraselenafulvalene (TTCn-TSeF, n = 1–15)

Abstract: A series of tetrakis(alkylthio)tetraselenafulvalene compounds (TTCn-TSeF, n = 1–15) were prepared by a one-step reaction between dialkyl disulfide and tetralithiated TSeF. Molecular properties (redox potentials and optical absorptions in solution) and solid-state properties (thermal behaviors, electric conductivities, and molecular and crystal structures for n = 1 and 10) were studied. TTCn-TSeF compounds are weak electron donor molecules and characterized by small on-site Coulomb repulsion. TTC1-TSeF has a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A series of tetrakis(alkylthio)tetraselenafulvalene compounds 95 ( n = 1–15) was synthesized in up to 84% yield by a one-step reaction of dialkyl disulfides 94 with tetralithiated tetraselenafulvalene 2 ( Scheme 31 ) [ 82 ]. Compounds 95 were found to be weak electron-donating molecules and to show low dark conductivity.…”
Section: The 14-diselenafulvene and 1458-tetraselenafulvalene Derivat...mentioning
confidence: 99%
See 1 more Smart Citation
“…A series of tetrakis(alkylthio)tetraselenafulvalene compounds 95 ( n = 1–15) was synthesized in up to 84% yield by a one-step reaction of dialkyl disulfides 94 with tetralithiated tetraselenafulvalene 2 ( Scheme 31 ) [ 82 ]. Compounds 95 were found to be weak electron-donating molecules and to show low dark conductivity.…”
Section: The 14-diselenafulvene and 1458-tetraselenafulvalene Derivat...mentioning
confidence: 99%
“…At the same time, as the number of methylene groups increased, the electrical conductivity increased due to the presence of high-dimensional conduction paths. The resulting compounds were highly soluble in organic solvents [ 82 ].…”
Section: The 14-diselenafulvene and 1458-tetraselenafulvalene Derivat...mentioning
confidence: 99%
“…Therefore, the structures of alkyl derivatives vary depending on the chain length. Accordingly, the alkylation of rigid molecules can alter their physical properties [1][2][3][4][5][6][7][8][9][10][11] significantly, including their thermal properties, [12][13][14][15] crystal structure, [16][17][18][19][20][21] and the structure of adsorbed monolayers. [22][23][24][25][26][27][28] We have analyzed the thermal properties of salen derivatives bearing alkyl chains of variable length and found that those with alkoxy groups adopt a liquid crystalline state at varying temperatures depending on the alkyl chain length.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of short alkyl side chains at the peripheral position of π‐conjugated rings usually decreases the attractive π‐π stacking interactions owing to steric repulsion between the alkyl groups, though the alkyl side chains endows higher donor ability, better solubility, and sometimes better stability to π‐conjugated molecules. In contrast to short alkyl chains, stacking ability of π‐conjugated molecules in the solid state is increased with long alkyl side chains, known as fastener effect, because the van der Waals interactions between the long alkyl side chains fasten the central π‐conjugated molecules tightly. The resulting columnar structure of the π‐part enhances the molecular overlap and π‐π stacking .…”
Section: Introductionmentioning
confidence: 99%